Long-term outcome and patterns of failure in patients with advanced head and neck cancer - Hauswald, Henrik; Simon, Christian; Hecht, Simone; Debus, Jürgen; Lindel, Katja (Radiation oncology, 2011)
To access the long-time outcome and patterns of failure in patients with advanced head and neck squamous cell carcinoma (HNSCC).
Gesehen am 23.09.2022